Dosimetric analysis of patients receiving radiotherapy with VMAT technique in localized prostate cancer and its correlation with side effects - ALSAN ÇETİN, İLKNUR (My University, 2023)
Aim: The aim was to study the relationship between dosimetric data of localized prostate cancer patients who have been treated with curative radiotherapy (RT) and gastrointestinal (GIS), genitourinary (GUS), anal and sexual side effects, and whether there was a difference between dosimetric data and clinical findings between risk groups. Methods: Eighty-seven patients who received curative radiotherapy for localized prostate cancer between 2014 and 2019 were included in the study. Dosimetrically; whether there was a relationship between V30, V40, V50, V60, V65, V70, V75 for rectum and bladder; D90 for the penile bulb, V72, V74, V76 for the bulbomembranous urethra, V30, V45, V53, Dmax for the anus, and V45 (cc) for the intestine data and the side effects were analyzed. It was evaluated whether there was a relationship between testosterone values and sexual side effects. The Kolmogorov-Smirnov test, one-way analysis of variance (ANOVA) (F-test), and paired-sample t-test were used as statistical methods. For statistical significance, P < 0.05 was accepted. Results: : The mean age of the patients was 69 (50-86), the mean Prostat specific antigen (PSA) (ng/dL) before RT was 25.1 (0.9-339), the median RT dose was 76 Gy (74-78 Gy), and the mean follow-up period was 38.2 months. PTVmax, PTVmean, PTVmin, bladder V40, bladder V50, rectum V30, rectum V40, rectum V50, and intestinal V45 (cc) were determined as dosimetric data showing differences between risk groups. A statistically significant relationship was found between rectum V30 (P = 0.017), V60 (P = 0.019), V65 (P = 0.008), V70 (P = 0.007), and V75 (P = 0.034) and chronic GIS side effects. G2 GIS side effects were observed in four patients (4.6%) in the entire patient group during the acute period. A statistically significant relationship was found between the patients receiving hormonotherapy (P = 0.021) and testosterone values at the last control (P ≤ 0.001) and chronic sexual side effects. Conclusion: Attention should be paid to the rectum V30, V60, V65, V70, and V75 values to minimize the long-term GIS side effects in patients who have undergone RT. Testosterone level and ADT status affect chronic sexual toxicity.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Nuclear medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ONKOLOJİ; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; ONCOLOGY; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiology, Nuclear Medicine and Imaging; External radiotherapy; normal tissue toxicity; prostate cancer